Влияние контактного трения на характер течения и силовой режим процесса прямого выдавливания с уширением - Кузьменко, Виктор Иванович; Горностай, В. М.; Василенко, В. О. (НТУ "ХПИ", 2013)
Работа посвящена усовершенствованию процессов холодного выдавливания профилей из конструкционных металлов и сплавов с раздачей для снижения усилий деформирования, повышения стойкости деформирующего инструмента и получения изделий повышенной надежности и долговечности. Особое внимание было уделено вопросам влияния трения на силовой режим и конечное формоизменение путём варьирования формой и шириной калибрующего пояска

This patent devoted for improvement the efficiency of processes of cold extrusion with dispensing of profiles for decreasing straining force, enhancing the durability of forming tool and obtaining products with enhanced dependability and durability. The modern industry needs the resource–saving and high-productive technologies of obtaining high-accuracy profiles made of constructional material s with mechanical properties of deformed metal which satisfy the application conditions. It is established that straight cold extrusion with dispensing is perspective way of obtaining profiles referred above
Keywords: напряженно-деформированное состояние; прямоугольный профиль; качество профилей; калибрующий поясок; стойкость деформирующего инструмента; cold straight extrusion; dispensing; mathematical models; power modes; specific stress; mode of deformation; rectangle profile; profile quality